Measuring fear among public transport users in urban cities - Sham, Rohana (2015)
This paper will discuss purely on the research methods used in this study where major independent and dependent variable of the study will be discussed especially on the methods of measurement on each variable involved in the environment management. It comprises of the information on the research design, sample selection through population and sampling, data collection, measurement techniques on each variables involved, instrumentation and method used for data analysis. The statistical method such as descriptive analysis, correlation, cross tabulation and a confirmatory analysis using AMOS used in analyzing the data was also discussed. Moreover the detail of an on board survey will also be discussed as a methods of data collection during the field work. The main aim of this paper is to describe the interrelationship factor between transport and urban environment that affect women?s fear. A set of questionnaire were used to measure the level of fear of women travellers based on several constructs of fear towards crime. The major contribution of this paper is the measurement procedure being carried out to meet the target objective of the study. A set of women commuters were selected and questionnaire were personally administered to ensure the validity of the sampling. A new psychological approach used in measuring the fear will also be discussed. This paper concludes with a detail measurement involve in measuring each variable involved in the study. Keywords: Measuring, Fear, Urban, Public transport,City.